KOMUNIKASI PEMASARAN DINAS PARIWISATA PROVINSI KEPULAUAN RIAU DALAM MENINGKATKAN KUNJUNGAN WISATAWAN - Ratna Puri Handayani; Nurjanah Nurjanah (Jurusan Ilmu Komunikasi Universitas Andalas, 2023)
Riau Islands Province in 2019 occupies the second position as foreign tourist arrivals in Indonesia. Based on statistical data, the Riau Islands Province also experienced an increase in visits by foreign and domestic tourists in 2015-2019. Based on this, it can be seen that the marketing communications have been successful. For this reason, this research was conducted with the aim of knowing and analyzing how marketing communications are carried out by the Tourism Office of the Riau Islands Province. This study used a qualitative method and the results were descriptive in nature by involving seven informants consisting of two main informants and five secondary informants. Collecting data in this study is using interview techniques, observation, and documentation. The results of the study show that the Tourism Office of the Riau Archipelago Province conducts marketing communications in the form of advertising, personal selling, digital and social media marketing, sales promotion, public relations and publicity, events and experiences, as well as word of mouth both directly and digitally.